IbM.KELOMPOK INDUSTRI SERBUK INSTAN JAMU DAN MINUMAN KESEHATAN DI UNGARAN, KABUPATEN SEMARANG - Handayani, Dwi; Ikhsan, Diyono; Murni, Murni; Ardiansari, Anindya (Universitas Diponegoro, 2014)
Abstract UMKM